2016
DOI: 10.2135/cropsci2015.08.0530
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Relationships in Breeding Lines and Cultivars of Brassica napus and Their Implications for Breeding Winter Oilseed Rape

Abstract: The level of genetic diversity or similarity between parents has been proposed as a predictor of F1 generation performance and heterosis for seed yield. The objective of this study was to determine the feasibility of using amplified fragment length polymorphism (AFLP) fluorescent‐labeled primers to evaluate the genetic relationships between 101 oilseed rape (Brassica napus L.) genotypes to maximize the selection of different parents in a breeding program. The collection of genotypes included 25 cytoplasmic mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…3) from other double low WOSR. The genetic diversity of resynthesized (RS) and semi-resynthesized (semi-RS) lines has also been demonstrated in studies of 101 breeding lines and WOSR cultivars using 10 AFLP primer combinations (Liersch et al 2016). Similar results were obtained by Sosnowska et al (2017) in investigations of collections of spring and WOSR cultivars, B. rapa and Brassica oleracea, as well as nearly 50 RS lines and semi-RS lines.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…3) from other double low WOSR. The genetic diversity of resynthesized (RS) and semi-resynthesized (semi-RS) lines has also been demonstrated in studies of 101 breeding lines and WOSR cultivars using 10 AFLP primer combinations (Liersch et al 2016). Similar results were obtained by Sosnowska et al (2017) in investigations of collections of spring and WOSR cultivars, B. rapa and Brassica oleracea, as well as nearly 50 RS lines and semi-RS lines.…”
Section: Discussionsupporting
confidence: 59%
“…The process of breeding hybrid varieties requires a large number of crosspollination combinations of parental lines and their evaluation in multiple field experiments, preferably in multiple environments in terms of general and specific combining ability, with simultaneous very careful selection of the components based on a number of qualitative characteristics (Bocianowski et al 2016). For this purpose, methods are sought that would allow the early selection of parental components of F1 hybrids, and thus the shortening of the breeding cycle (Liersch et al 2016). Such studies performed in different species of plants have shown that one of the elements allowing a high heterosis effect to be obtained in the yield of seeds is the genetic distance (GD) of the parental forms used to make the F1 hybrid.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their wide adaptation and ability to thrive under varying agroclimatic conditions, brassica crops are grown throughout the world for food, animal forage, fodder and industrial applications (Eckes et al 2017). In Poland within Brassica species, winter oilseed rape is the most important oil-protein plant (Liersch et al 2016;Szała et al 2016;Sosnowska et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the last 15 years, the global production of rapeseed has doubled, reaching over 60 million tons, with a grain production of almost 71 million tons recorded in the marketing year of 2018/2019 [1]. In Poland and other European countries characterized by moderate climate conditions, winter oilseed rape (WOSR) is considered as the most important oil-protein crop [2][3][4][5]. Since the 1960s, there has been a strong selection pressure to develop double-low (canola) oilseed rape producing seeds characterized by a very low content of erucic acid (C22:1, no more than 2%) and a significantly lowered glucosinolates (GLS) content (less than 25 µmole g −1 of seeds), as compared to over 50% of erucic acid and until 160 µmole g −1 of seeds of GLS, respectively, in the 'traditional' oilseed rape cultivars.…”
Section: Introductionmentioning
confidence: 99%